2013
DOI: 10.4187/respcare.01734
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Patients With Interstitial Lung Diseases Fail in the ICU? A 2-Center Cohort Study

Abstract: BACKGROUND: Admitting patients with interstitial lung disease (ILD) to the ICU is controversial, due to their associated high mortality when they require invasive mechanical ventilation. We aimed to determine the risk factors for mortality in ILD patients requiring ICU support due to acute respiratory failure. METHODS: An observational cohort study was performed in 2 chest diseases teaching hospitals. We included all ILD patients with acute respiratory failure admitted between 2008 and 2010. Subject demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…Small, retrospective studies have reported some success with noninvasive positive pressure ventilation (NIV) with improved mortality compared with invasive mechanical ventilation (IMV) with survival in responders to NIV of around 40%. [14][15][16][17] As with most data in ILD, these studies are predominantly done with patients with IPF, because it is the most common ILD. Additionally, a selection bias for less severely afflicted patients may be present in those who are able to be supported by NIV as compared with those who ultimately require IMV.…”
Section: Ventilatory Strategies Noninvasive Ventilationmentioning
confidence: 99%
“…Small, retrospective studies have reported some success with noninvasive positive pressure ventilation (NIV) with improved mortality compared with invasive mechanical ventilation (IMV) with survival in responders to NIV of around 40%. [14][15][16][17] As with most data in ILD, these studies are predominantly done with patients with IPF, because it is the most common ILD. Additionally, a selection bias for less severely afflicted patients may be present in those who are able to be supported by NIV as compared with those who ultimately require IMV.…”
Section: Ventilatory Strategies Noninvasive Ventilationmentioning
confidence: 99%
“…However, the low incidence of ILD-associated ARF requiring ICU admission has been a major obstacle to research into outcome predictors and treatment optimisation. In two studies, mortality was high, from 47% overall to 89.7% among patients who required invasive mechanical ventilation [7], [8]. As a result, intensivists may be reluctant to admit patients with ILD and ARF [8].…”
Section: Introductionmentioning
confidence: 99%
“…Given the poor prognosis of patients who require mechanical ventilation, some have suggested that noninvasive ventilation would be a good strategy for patients with clinical deterioration and idiopathic pulmonary fibrosis. Small, retrospective studies have shown improved outcomes in AE-IPF patients supported with noninvasive positive pressure ventilation (NIPPV) [22][23][24], however a selection bias may account for the better prognosis as patients who can be successfully supported with NIPPV are likely less ill. Of the patients in these studies who failed NIPPV, mortality was reported as 85-100% [22][23][24].…”
Section: Noninvasive Ventilationmentioning
confidence: 99%